Expressão da variância genética oculta e associação dos efeitos genéticos à desmama com crescimento pós-desmama de bovinos sob parasitismo - Adriane Rafaela Barbosa (2016)
The expression of cryptic genetic variance and association between genetic effects at weaning with post-weaning growth of cattle under parasitism. The objective of this work was to evaluate the effect of increasing parasite burden on genetic parameters for growth traits of cattle. We used 16,654 records of weaning weight (W205) of Nellore calves (males and females) and 1,101 records of post-weaning average daily gain (ADG) of Nellore young bulls. The ADG records were obtained in 32 performance tests on pasture, with animals between 330 and 550 days of age. The animals were classified in groups with low or high tick and gastrointestinal nematode (GIN) burdens. Genetic variances and heritability for ADG at low tick burdens (1,154 and 0.21) and low GIN burdens (1,965 and 0.36) were lower than genetic variances and heritability for ADG at high tick burdens (4,138 and 0,64) and high GIN burdens (4,173 and 0.63). The genetic correlations between the direct effect of W205 with direct effect of ADG under high tick and GIN burdens were positive (0.49 and 0.50, respectively). The same parameters were not different of zero when the ADG was measured in groups of animals under low tick (-0.20) and low GIN (0.06) burdens. The genetic correlations between the maternal effect of W205 with direct effect of ADG under high tick and GIN burdens were -0.33 and -0.28, respectively. Genetic correlations between maternal effect of W205 with direct effect of ADG under low tick and GIN burdens were 0.57 and 0.45, respectively. Raising of young bulls under high parasitic burden, but within limits that do not harm the animal performance, allows the expression of the cryptic genetic variance for growth traits of cattle. Response to selection for post-weaning growth of cattle under low parasite challenge is lower than response to selection for growth under high parasite challenge.